2019
DOI: 10.1097/sla.0000000000003452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Intraoperative Near Misses in Laparoscopic Rectal Cancer Surgery

Abstract: Objective: To investigate the frequency, nature, and severity of intraoperative adverse near miss events within advanced laparoscopic surgery and report any associated clinical impact. Background: Despite implementation of surgical safety initiatives, the intraoperative period is poorly documented with evidence of underreporting. Near miss analyses are undertaken in high-risk industries but not in surgical practice. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Patients with higher recorded rates of errors had more early postoperative complications. Cases with a significant intraoperative event demonstrated significantly greater number of 'near misses' , compared to cases without significant intraoperative events [49].…”
Section: Technical Skill Influences Clinical Outcomesmentioning
confidence: 90%
See 2 more Smart Citations
“…Patients with higher recorded rates of errors had more early postoperative complications. Cases with a significant intraoperative event demonstrated significantly greater number of 'near misses' , compared to cases without significant intraoperative events [49].…”
Section: Technical Skill Influences Clinical Outcomesmentioning
confidence: 90%
“…Surgical errors and poor technical skill in laparoscopic colorectal and UGI surgery are associated with an increased risk of postoperative mortality and morbidity [48][49][50]. Twenty bariatric surgeons from the United States of America (USA), each submitted a single representative laparoscopic gastric bypass video with clinical data for peer-peer assessment of technical skills.…”
Section: Technical Skill Influences Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empfehlungen wie Fehler vermieden werden können, bevor sie entstehen, sog. Predictive Analytics [14].…”
Section: Ki Und Chirurgische Performanceunclassified
“…This open‐ended approach captures events that are workflow deviations from a pre‐defined best practice (eg, oesophageal intubation), unusual events that cause no harm (eg, provider tripping over wires), or events unrelated to care that create unsafe situations (eg, power outage) 1,3,5 . Most of these studies have found that errors directly causing harm are uncommon, but events that are latent safety threats are frequent and could be precursors to adverse events 1,5,8‐10 . Proper identification and analysis of NREs that represent latent safety threats may facilitate the development of approaches for preventing or mitigating associated harm.…”
Section: Introductionmentioning
confidence: 99%